2020
DOI: 10.20471/acc.2020.59.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Interleukin-6, C-Reactive Protein and Interleukin-6 (-174) G/C Polymorphism in the Pathogenesis of Crohn’s Disease and Ulcerative Colitis

Abstract: -Inflammatory bowel diseases are multifactorial disorders the clinical manifestation of which depends on the interaction among immune response, genetic and environmental factors. There is growing evidence that cytokines and gene polymorphisms have an important role in disease pathogenesis in various populations although molecular mechanism of their signaling and interactions is not fully understood yet. The present study aimed at exploring the effects of interleukin-6, C-reactive protein and interleukin-6 rs18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…Boris Takač and colleagues also observed significant differences in IL-6 levels between patients with IBD and healthy subjects. 60 Poullis et al [61][62][63] found higher CRP concentrations in patients with CD. We observed high levels of all inflammatory markers in all patients, especially in those with active disease, which is consistent with the aforementioned findings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Boris Takač and colleagues also observed significant differences in IL-6 levels between patients with IBD and healthy subjects. 60 Poullis et al [61][62][63] found higher CRP concentrations in patients with CD. We observed high levels of all inflammatory markers in all patients, especially in those with active disease, which is consistent with the aforementioned findings.…”
Section: Discussionmentioning
confidence: 95%
“…Boris Takač and colleagues also observed significant differences in IL‐6 levels between patients with IBD and healthy subjects 60 . Poullis et al 61–63 found higher CRP concentrations in patients with CD.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have clearly suggested that common genetic components may underlie different immune-related diseases ( 38 , 39 ). The etiopathogenesis of IgAV is complex and not fully understood, and may involve a number of interactions between various environmental and genetic factors ( 10 , 11 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a common pro-inflammatory cytokine. It has been shown that serum levels of this pro-inflammatory cytokine were significantly increased in IBD patients [18]. Further research found a correlation between IL-6 expression and disease activity in patients with Crohn's disease (CD) and UC [19].…”
Section: Discussionmentioning
confidence: 99%